Subsequent musculoskeletal injury incidence are similar between general infection and COVID-19 among high school athletes in the Unites States despite higher illness incidence during academic years 2019-2020 and 2020-2021 - Shanley, E.; Thigpen, C. A.; Prats-Uribe, A.; Norhen, T.; Staley, T.; Bullock, G. S. (Journal of Orthopaedic & Sports Physical Therapy, 2022)
Objective: 1) Describe overall illness, and COVID-19-specific illness in high school athletes in the 2019-2020 and 2020-2021 academic school years; and 2) describe and assess the risk of musculoskeletal injury following general infection, and after COVID-19. Design: Ecological study Methods: High schools (6 states; 176 high schools) were matched between the 2019-2020 and 2020-2021 academic school years, based on 2020-2021 high school sport participation. Illness and injury data were collected from the high school athletic trainers. Illness was stratified by overall illness, general infection, and COVID-19. Injuries following moderate or severe infections or COVID-19 were recorded. Illness and injury incidence rate per 100 athletes per year with 95% confidence intervals (95% CI) were calculated. Negative binomial models comparing injury following general infections and COVID-19 infections were calculated. Results: 98,487 and 72,521 athletes participated in the 2019-2020 and 2020-2021 years. Illness incidence rate was less in the 2019-2020 [0.30 (95% CI: 0.27-0.34)] than 2020-2021 [1.1 (1.0-1.2)] year, resulting in a difference of 0.8 (95% CI: 0.7, 0.9). COVID-19 incidence rate was 0.52 (0.47-0.58) in the 2020-2021 year. Injury following general infection incidence rate was 27.9 injuries (21.4-34.5) per 100 athletes in 2019-2020, and 22.5 injuries (19.3-25.7) per 100 athletes in 2020-2021. There was no difference in injury risk following general infection and COVID-19 [Rate Ratio: 1.2 (95% CI: 0.7-2.4)]. Conclusions: The incidence rate for all illnesses in high school athletes was slightly (0.8) greater in the 2020-2021 academic compared to the 2019-2020 year. Most of the incidence increase was due to infections and COVID-19. Subsequent injury incidence following moderate and severe infections were similar between years and between general infections and COVID-19.